Transforming Islamic Educational Services: The Role of Banking Synergies in Enhancing Infrastructure and Programmatic Innovation in Pesantren - Wahid, Abd Hamid; Mashudi, Mashudi; Ridlo, Moh Khusnur (JURNAL AL-TANZIM, 2026)
This study aims to analyze how community-based Islamic boarding school financing management synergizes with banking institutions to strengthen educational services. Islamic boarding schools have long played a strategic role in Indonesia's academic and social development; however, many face ongoing challenges related to financial sustainability, service quality, and managerial capacity amidst global change. This research uses a qualitative case study approach. Data were collected through interviews, observation, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal three primary outcomes: first, synergy with banking institutions enables infrastructure development, program innovation, and the provision of scholarships that directly improve the quality of educational services. Second, improved financial governance, transparency, and access to financing strengthen institutional trust and operational sustainability. Third, integrating ZISWAF management and financial literacy programs empowers both institutions and students, engaging government, industry, academia, the community, and the environment. This study contributes to the Islamic education management literature by introducing an ecosystem-based financing perspective and by recommending broader policy support and future mixed-methods research to inform large-scale, inclusive Islamic boarding school financing models.